Chronic lymphocytic leukemia and light chain proximal tubulopathy: A rare presentation of a common disease. Issue 1 (June 2022) - Klomjit, Nattawat; Zand, Ladan; Grande, Joseph P; Leung, Nelson
Chronic lymphocytic leukemia (CLL) is the most common leukemia in developed countries. Kidney injuries related to CLL can occur via several mechanisms. Approximately 30%–40% of CLL patients with a kidney biopsy have monoclonal-protein related lesions. However, such lesions mostly involve glomeruli with only rare instances of tubule-interstitial disorders. There is only a single case report of a CLL patient who presented with crystalline light chain proximal tubulopathy (LCPT). Fanconi syndrome (FS) may provide clinical clues in these patients. We report a case of a CLL patient who presented with hypokalemia in the setting of advanced kidney failure in which serum monoclonal IgG kappa was detected. The patient demonstrated typical signs and symptoms of FS. The urinary retinol binding protein was also extremely elevated (638 times upper normal limit). A kidney biopsy revealed non-crystalline LCPT with CLL infiltration. FS in CLL is an extremely rare presentation, as only four cases had been previously reported. Of these, only a single case had crystalline LCPT. Our case is the first report of non-crystalline LCPT in a CLL patient. Obinutuzumab and Venetoclax were started to address the CLL, and an improvement in kidney function was noted thereafter.